THE EFFECT OF SEVERAL CONCENTRATIONS OF SAKAWA PLANT GROWTH REGULATOR ON SEED GERMINATION AND SEEDLING GROWTH OF LERAK (Sapindus rarak DC) ON COMPOST MEDIA - Nurul Sumiasri; Dody Priadi; I.N.K. Kabinawa (Universitas PGRI Semarang, 2011)
Study of the effect of several concentrations of plant growth regulator (Sa-kawa) on seed germination and seedling growth of lerak (Sapindus rarak D.C ) on compost media was carried out in the Plant and Animal Germplasm Garden of Cibinong. The objective of this study was to know optimum concentration of plant growth regulator on growth of lerak This study was arranged by using randomized complete design (RCD) with 3 (three) replications. The treatments of concentrations variation of plant growth regulator i.e.?é?á 0 (control), 1, 2 and 3 ml/l were used. Each treatment consists of 5 samples (individuals).. The results showed that?é?á the good concentration to the growth parameter?é?á such as growth percentage, plant height, total leaves, root length and total root were 2 ml of Sakawa in?é?á 1ml/l (one liter of water). Keywords: sakawa plant growth regulator, growth, seedling, Sapindus rarak compost